2006
DOI: 10.1007/s10800-006-9166-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behaviour of retrogressed and reaged (RRA) 8090 and 1441 Al–Li–Cu–Mg–Zr alloys

Abstract: 8090 and 1441 Al-Li-Cu-Mg-Zr alloys of peak aged T8 tempers were subjected to retrogression treatment followed by reageing to peak aged (RRA) T77 tempers. Electrochemical polarization studies were carried out on the alloys of T8, T77 and over aged T7 tempers, in 3.5% NaCl, 3.5% NaCl + 0.1M LiCl + 0.3% H 2 O 2 and 3.5% NaCl + 0.1M LiCl + 0.7% H 2 O 2 solutions. The shape of the polarization curves is similar for all the tempers of both alloys in all environments. The corrosion rates are more or less the same ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…710 such as corrosion potential (E corr ), corrosion current density (i corr ), passivation current (i p ) of different alloy tempers in different environments. These values, including the i p , are in close match with values reported in literature [5,6]. E corr and i corr values of the alloy tempers in different environments are determined by Tafel extrapolation method.…”
Section: Electrochemical Corrosion Behavioursupporting
confidence: 88%
See 1 more Smart Citation
“…710 such as corrosion potential (E corr ), corrosion current density (i corr ), passivation current (i p ) of different alloy tempers in different environments. These values, including the i p , are in close match with values reported in literature [5,6]. E corr and i corr values of the alloy tempers in different environments are determined by Tafel extrapolation method.…”
Section: Electrochemical Corrosion Behavioursupporting
confidence: 88%
“…Literature [4][5][6] reveals the electrochemical behaviour of the precipitation hardanable aluminum alloys of various aging tempers which affect in controlling the size, distribution and volume fraction of the second phase precipitates within the grains, along the grain boundaries and precipitate free zone (pfz) width as well. Further, several researchers have investigated stress corrosion cracking and hydrogen embitterment behaviour of Al-Zn-Mg-(Cu) alloy in various environments and correlated the microstructure with different heat treatments and aging schedules with stress corrosion behaviour [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The precipitates itself have little influence on the pitting potential but on the kinetics of corrosion, either acting as local cathodes or being dissolved and disappear from the surface or cause selective corrosion. Figure 3 indicates the presence of higher amounts of anodic phases in alloy tempers with increasing aging time and these findings have also been reported by the authors and other researchers 5, 6, 8, 12, 23, 24, 27, 29.…”
Section: Resultssupporting
confidence: 86%
“…Electrochemical investigation and corrosion behaviour were carried out on AlLiM (M = Cu, Mg and Zr) alloys by several investigators 4, 9–21 and there are considerable differences in opinion between researchers about the corrosion behaviour of these alloy tempers. Lane et al 15 studied a comparison of corrosion behaviour of lithium containing aluminium alloys and conventional aerospace alloys, and they observed that the AlLi alloys are also susceptible to localised pitting, exfoliation, galvanic, etc.…”
Section: Introductionmentioning
confidence: 99%